Military Training Mission in Iraq: An Exploratory Case Study Research - Reis, João (2021)
The purpose of this paper is to investigate how military training is being conducted by NATO coalition forces in Iraq. Thus, the intent of this paper is to discuss the implications of existing misalignments between the military forces that are providing the training and those receiving it. To that end, we have used an exploratory case study research, which included multiple sources of data collection for corroboration and triangulation purposes. The results that emerged from the content analysis showed two types of outcomes that may be relevant to improve the military training in Iraq. The first outcome is identified as the intangible actions, which were mainly focused on social relations, with the intent of narrowing the cultural gap between the international coalition and Iraqi forces. Without surprising, a second outcome is identified as tangible actions, which were associated with training programs and the establishment of tactics, techniques, and procedures (TTPs) relevant to small and medium military units. Future research should focus on programs of “training the trainers” in order to develop long-term teaching and move forward with sustainable Iraqi Security Forces (ISF).